The carbon allotrope glitter as n-diamond and i-carbon nanocrystals - Bucknum, Michael J. (2011)
Diffraction data taken from nanocrystalline n-diamond and i-carbon forms is fit to a so-called glitter model, in which the geometry of the C lattice has been optimized by density functional theory (DFT). A calculated theoretical diffraction pattern for glitter is shown to be a close fit to the experimental data for these novel C forms.